Hermeneutic explication versus the explanation of social facts: A comparison of Durkheim’s and Giddens’ rules of sociological method - Đorić, Gorana D. (Sociološki pregled, 2018)
The paper reexamines methodological implications of ontological assumptions of positivistic and interpretative approach to social phenomena by comparing Durkheim’s’ and Giddens’ rules of sociological method. The novelty is that the assumptions of the two approaches are interpreted not as overwriting each other, but as defning the conditions under which one or the other approach is better suited for any given analysis. The analysis fnds that the method of interpretation is justifed if the question is how actors generate social interactions, if the outcomes of actions are intended, and in cases when behavioral patterns are poorly institutionalized. Positivistic approach is merited when explaining social interaction by reference to its structural properties, if the outcomes of actions are unintended, and in cases when social relations are sufciently reifed.